WASP-120 b, WASP-122 b, and WASP-123 b: Three Newly Discovered Planets from the WASP-South Survey. (17th May 2016) - Turner, O. D.; Anderson, D. R.; Cameron, A. Collier; Delrez, L.; Evans, D. F.; Gillon, M.; Hellier, C.; Jehin, E.; Lendl, M.; Maxted, P. F. L.; Pepe, F.; Pollacco, D.; et al.
Abstract: We present the discovery by the WASP-South survey of three planets transiting moderately bright stars (V ≈ 11). WASP-120 b is a massive (4.85 M Jup ) planet in a 3.6-day orbit that we find likely to be eccentric ( e = 0.059 − 0.018 + 0.025 ) around an F5 star. WASP-122 b is a hot Jupiter (1.28 M Jup, 1.74 R Jup ) in a 1.7-day orbit about a G4 star. Our predicted transit depth variation caused by the atmosphere of WASP-122 b suggests it is well suited to characterization. WASP-123 b is a hot Jupiter (0.90 M Jup, 1.32 R Jup ) in a 3.0-day orbit around an old (∼7 Gyr) G5 star.